(untitled) (Scientific journal of the Fergana State University, 2023)
This article reflects on the activities of the Oliy Majlis of the Republic of Uzbekistan, adapting to the conditions of the pandemic and effectively using the possibilities of information technologies, in connection with the adoption of legislative documents and the control of their execution. Also, the formation of a mechanism to ensure the activity of the Committee on Defense and Security Issues of the Legislative Chamber of the Oliy Majlis in terms of information and analysis, as well as to ensure the activity of the Legislative Power body is more open, to deliver the work being carried out by the corps of deputies to the general public, deputies and voters The necessity of further development of feedback between